Autologous bone marrow‐derived cells with placental extract for healing excisional cutaneous wounds in animal model. Issue 2 (11th April 2012) - Akela, Ashok; Nandi, Samit Kumar; Das, Partha; Banerjee, Dibyajyoti; Roy, Subhasis; Datta, Uttam
<x xml:space="preserve">Abstract</x> Topical wound‐healing potential of autologous bone marrow‐derived nucleated cells along with placental extract was evaluated in comparison with buffy coat of autologous blood on full‐thickness cutaneous wounds in the thoracolumbar region of 15 clinically healthy New Zealand rabbits. Three wounds of 2 × 2 cm, one on the right side of the body and two on the left side of the midline were created on the dorsal lumbar region of each rabbit under xylazine–ketamine anaesthesia. The wounds of each animal were randomly assigned to one of the three treatments: topical application of autologous bone marrow‐derived cells with placental extract (group I), application of buffy coat in the autologous plasma with placental extract (group II) and autologous plasma with placental extract as control (group III). Wounds were observed for 30 days macroscopically and for granulation tissue formation, histomorphological and histochemical evaluation. Time of appearance of granulation tissues and filling of wound beds were faster in group I followed by group II and group III animals, respectively. Histomorphological findings exhibited an earlier disappearance of inflammatory reaction, better epithelialisation, significantly maximum neovascularisation, fibroplasias and collagenation in group I followed by group II and group III animals, respectively. Histochemical findings also depicted maximum number of robust, thick, interwoven type of collagen fibres, stout, highly tortuous and interwoven network of elastin fibres and numerous mesh war form of reticulin fibres within the dermal component were present in group I when compared with group II and III animals. Experiment conclude that single application of autologous bone marrow‐nucleated cells with placental extract topically could be a novel option for faster healing in complicated non healing wounds both in human beings and animals.